Infectious Diseases : Atlas, Cases, Text - Cooke, Robin A. (Sydney, New York McGraw-Hill, 2008)
"Infectious diseases. High quality illustrations of tropical and other infectious diseases. Emphasis is placed on the clinical presentation and laboratory diagnosis of the diseases considered. Authors hope that this atlas will be of use to students in all fields of biological study, to clinical and laboratory health workers, to travel medicine doctors and perhaps even to specialist infectious disease physicians who may only need to borrow some of the images for their lecture presentations."--Provided by publisher.
Include Index and Illustration
Keywords: Communicable diseases